Agronomic and socio-economic drivers of fertilizer use and crop productivity in smallholder wheat production systems in Ethiopia - Ebrahim, Mohammed; Mesfin, Tewodros; Tamene, Lulseged; Liben, Feyera; Abera, Wuletawu; Tilaye, Asmalu (Springer Nature Link, 2024)
Wheat (Triticum aestivum L.) is crucial for global food security and a staple crop in Ethiopia, yet farmer yields remain low, averaging 2.7 t ha⁻ compared to over 5 t ha⁻ at research stations. This study investigates the impact of socio-economic factors, local agronomic practices, and site-specific fertilizer management on wheat production in Goba, Lemu, Siyadebr, and Basona districts of Ethiopia. A survey of 228 households analyzed the influence of these factors on wheat productivity and fertilizer use, employing descriptive statistics, t-tests, and regression models. Results indicated that crop residue retention, improved wheat varieties, and organic fertilizers significantly increased yields, while row fertilizer application at planting had a negative effect. Fertilizer application rates varied significantly among farmers and were influenced by practices like top-dressing, monocropping, and participation in agricultural training. District-level differences in yield and fertilizer response highlighted the need for site-specific management. Multiple regression analysis revealed that key predictors of fertilizer use included cultivated land area, household income, education, small ruminant ownership, and extension contact, with larger land ownership, higher income, organic fertilizer use, and extension access being the most significant. Average yield increases due to site-specific fertilizer applications varied across districts. Overall, significant yield gains were achieved through site-specific fertilizer application across the four districts, with an average yield of 5.3 Mg ha⁻ , compared to approximately 4 Mg ha⁻ using the local farmers' fertilizer application rates. This study underscores the importance of considering local agroecological conditions in fertilizer management to boost wheat productivity and support food security and economic development in Ethiopia.